ANALISIS PENGARUH VARIABEL MAKRO EKONOMI, DENGAN DEMOGRAFI DAN EFEK KRISIS KEUANGAN GLOBAL SEBAGAI VARIABEL KONTROL TERHADAP PEMBIAYAAN BANK SYARIAH DI INDONESIA (Studi pada Bank Syariah Devisa di Indonesia Periode 2007-2016) - Dwijaya, Putra Agung; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2018)
This research was conducted to examine the influence of macroeconomic factors, as measured by inflation, interest rate, REER exchange rate and GDP growth to financing Islamic bank in Indonesia. This study also used control variables of demography (number of Muslim population in Indonesia) and the global financial crises effect in 2008. Data used this study was obtained from the Financial Report of Bank Indonesia publications, and bank report through the website. The sampling technique used was purposive sampling. The sample in this study 6 Sharia foreign exchange banks. Data analysis techniques used in this study is multiple regression on panel data, where there are 6 Sharia foreign exchange banks and 40 periods (quarterly data 2007 – 2016). There are two research models, in the model I the regression of macroeconomic variables to Islamic bank financing. Whereas in the model II the regression of macroeconomic variables to Islamic bank financing, demography and the global financial crises effect as a control variable. The result of this research is, in the regression model I variable inflation have positive and significant effect to Islamic bank financing, while the variable interest rate, REER exchange rate, and GDP growth have a negative and significant effect to Islamic bank financing. Whereas in regression model II, inflation have a positive and significant effect on Islamic bank financing, the REER exchange rate have a negative and significant effect on Islamic bank financing. There are differences where the variable interest rate and GDP growth have insignificant effect to Islamic bank financing. Control variables demography have a significant effect while the global financial crises effect have insignificant effect to Islamic bank financing.